Noise pollution: the silent killer of the century - Chaudhary, Ansh; Chaudhary, Bhupendra (International Journal Of Community Medicine And Public Health, 2020)
Labelled as ‘silent killer’ of 21st century, the noise pollution is largely neglected despite its short and long-term ramifications on human health. The noise affects the human beings from intrauterine life to old age in different ways. The ill effects of noise pollution are slow but cumulative in nature with long term health hazards in form of noise induced hearing loss, sleep disturbances, cardiovascular disease and stress etc. The increasing industrialization and modernization have rewarded us with noise as a pollutant so the accusing finger is clearly pointing towards the human activities. The various permissible noise limits in residential, commercial and industrial area should be strictly followed in consonance with the governing law. The violation of these limits should have strict legal consequences.